O304 alleviates abdominal aortic aneurysm formation via AMPK/mTOR/MMP pathway activation - Daohan Sun; Yaming Du (Frontiers in Pharmacology)
BackgroundAbdominal aortic aneurysm (AAA) rupture is a significant cause of mortality in the elderly population. Despite experimental models identifying promising pharmacological therapies, there is still a lack of pharmacological interventions for AAA prior to surgery. This study aims to evaluate the regulatory role of the novel adenosine monophosphate-activated protein kinase (AMPK) agonist O304 in AAA formation and explore its underlying molecular mechanisms.MethodsWe evaluated the expression of AMPK signaling pathway components and contractile vascular smooth muscle cell (VSMC)-related genes in AAA samples from mice using reverse transcription-quantitative polymerase chain reaction (RT-qPCR). We evaluate the TGF-β expression by western blotting and RT-qPCR and TGF-β concentration in blood by ELISA. We developed an in vitro model of transforming growth factor-β (TGF-β)-induced VSMC phenotypic switching. After treatment with O304, we analyzed the expression of contractile genes and proteins in VSMCs by immunofluorescence and Western blotting. We also evaluated the expression of AMPK signaling pathway components and matrix metalloproteinases by western blotting and immunofluorescence analysis. We established a mouse model of AAA to evaluate the impact of O304 on aneurysm diameter and blood pressure, analyzed VSMC phenotypic switching through immunofluorescence analysis, and assessed the regulatory effects of O304 on AMPK signaling in the mouse model of AAA by Western blotting.ResultsAMPK signaling pathway components and contractile genes in VSMCs were downregulated in mouse AAA samples, underscoring the crucial role of AMPK signaling in VSMC phenotypic switching. In the TGF-β-induced model of VSMC phenotypic switching, O304 activated AMPK signaling and prevented VSMC phenotypic switching from the contractile to the synthetic phenotype. Moreover, O304 significantly activated AMPK signaling, increased the proportion of contractile VSMCs, and reduced AAA formation and blood pressure in the mouse model of AAA.ConclusionDuring AAA development, VSMCs transitioned from the contractile to the proliferative phenotype, a process that has previously been associated with AMPK pathway inhibition. O304, an AMPK agonist, activated the AMPK pathway, preventing VSMC phenotypic switching and inhibiting AAA formation. These findings highlight the therapeutic potential of targeting the AMPK pathway in AAA.